Pelimpahan Wewenang Ajaran â€œHisbahâ€ di Indonesia - Asnawi, M. Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
The style o f government which was used by prophet Muhammad SAW attention to good intellectvalue. He orderedâ€œAmar Maâ€™ruf Nahi Munkar